A New Enantioselective Synthesis of the Anti-Parkinson Agent Safinamide - Reddi, Anjaneyulu; Mujahid, Mohammad; Sasikumar, Murugesan; Muthukrishnan, Murugan (Synthesis, 2014)
An alternative highly enantioselective synthesis of the anti-Parkinson agent safinamide from simple, commercially available, starting materials is described. The protocol might also be useful in the synthesis of structural variants of safinamide, such as ralfinamide or related analogues
Keywords: medicinal chemistry; stereoselective synthesis; amides; safinamide